ENTREPRENEURIAL ORIENTATION, NETWORKING, EXTERNAL ENVIRONMENT, AND FIRM PERFORMANCE: A CRITICAL LITERATURE REVIEW - James M. Gathungu; Dennis M. Aiko; Vincent N. Machuki (European Scientific Journal, ESJ, 2014)
The needs to conceptualize and empirically examine the context in which levels of analysis in entrepreneurship research are focused also influence entrepreneurial activities and policies. This literature review is intended to provide insights and guide empirical research to address knowledge gaps in entrepreneurial research. One of the primary topics of interest has been the characteristics of entrepreneurial organizations, often referred to as entrepreneurial orientation of the firm. Analysis of past literature has indicated the existence of empirical concerns on the Entrepreneurial orientation – performance relationship. However, there is little empirical research on how entrepreneurs neither harness the potential of networking nor is much known about how such initiatives work. Some researchers have also raised issues relating to the important theoretical arguments that are anchored on the dimensionality of Entrepreneurial orientation. A study of Entrepreneurial orientation and networking configurations open new areas to theory building research as it focuses attention towards complex relationships among entrepreneurial activities. The current study on past contributions in this stream of literature, seeking to provide definitive evidence of previously examined relationships between entrepreneurial orientation and performance as impacted by the networking and environment.